An Approach from Formative to Constructive Evaluation through an Autonomous Learning Process - Marcela Del Campo; Martha Isabel Bonilla; Luz Stella Ahumada (Asociación Colombiana de Profesores de Ingles, 2010)
The present text seeks to encourage a reflection around the meaning and possibilities of the evaluation of learning from a formative view and to focus on the aim to move towards a constructive evaluation that responds to the necessities of our students. This implies a continuous process that could be a fundamental source to get teachers aware of their role as a guide and, most importantly, help students make relevant decisions to achieve meaningful English learning through autonomy, a main element of constructive evaluation.